2013
DOI: 10.2139/ssrn.2308787
|View full text |Cite
|
Sign up to set email alerts
|

Intraday Volatility Forecast in Australian Equity Market

Abstract: On the afternoon of May 6, 2010 Dow Jones Industrial Average (DJIA) plunged about 1000 points (about 9%) in a matter of minutes before rebounding almost as quickly. This was the biggest one day point decline on an intraday basis in the DJIA's history. An almost similar dramatic change in intraday volatility was observed on April 4, 2000 when DJIA dropped by 4.8%. These historical events present very compelling argument for the need of robust econometrics models which can forecast intraday asset volatility. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The sigma forecast plot and the VaR backtesting plot for the MC-GARCH(1,1) model under the skewed Student's-t distribution are displayed below in Figures 7 and 8 respectively. As noted in Singh et al (2013), the spikes in the VaR forecasts as shown in the backtest plot in Figure 8 is due to the seasonal component during the opening of each trading day.…”
Section: Backtesting Var Using An Asymmetric Loss Functionmentioning
confidence: 75%
See 2 more Smart Citations
“…The sigma forecast plot and the VaR backtesting plot for the MC-GARCH(1,1) model under the skewed Student's-t distribution are displayed below in Figures 7 and 8 respectively. As noted in Singh et al (2013), the spikes in the VaR forecasts as shown in the backtest plot in Figure 8 is due to the seasonal component during the opening of each trading day.…”
Section: Backtesting Var Using An Asymmetric Loss Functionmentioning
confidence: 75%
“…Therefore, it can be concluded that the MC-GARCH models are able to forecast accurately the risk measure ES. As noted in Singh et al (2013), the spikes in the VaR forecasts as shown in the backtest plot in Figure 8 is due to the seasonal component during the opening of each trading day.…”
Section: A Regression-based Es Backtesting Procedure: the Bivariate Ementioning
confidence: 75%
See 1 more Smart Citation
“…Subsequent studies have only reinforced the previous findings. Singh et al (2013) applied the MC-GARCH model to three high frequency intraday intervals of 1 min, 5 min and 10 min for Australia's S&P/ASX-50 stock market and found that the model fit well to the intraday returns. This was supported by Diao and Tong (2015) who used the 5-min returns of the CSI 300 index.…”
Section: Introductionmentioning
confidence: 99%
“…Another context where the implementation of VaR and ES models is relatively under-developed is the currency exchange market. Most studies seem to test the performance of VaR and ES models using stocks or stock indices, see for example the studies of Palaro and Hotta (2006), Ruppert and Matteson (2011) or Singh et al (2013). Among all the financial asset markets, the currency market is the largest one in the world in terms of trading volume.…”
Section: Introductionmentioning
confidence: 99%